Mapping of Tsunami Disaster Mitigation Evacuation Routes of the Movement of the Sunda Subduction Megathrust (Case Study: Coastal Analysis of Southern Garut Regency) - Sapanji, R. A. E. Virgana Targa; Hamdani, Dani (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 2 No 1 (2020): The 2nd International Conference on Engineering, Technology, and Social SciencesDO - 10.18860/iconetos.v2i1.1258, 2021)
Potential disaster due to the movement of the subduction zone between the Eurasian Plate and the Indo-Australian plate, extending from the west of Sumatra to the south of Java, Bali, and Nusa Tenggara. This subduction zone is called the Sunda subduction arc. It has several segments. The Java segment has a lower seismic magnitude and frequency. Megathrust is a shallow part of the subduction lane which has a shallow dive angle, so the impact on the southern part of Garut Regency has the potential for earthquake and tsunami disaster, has been analyzed spatially and geoprocessing with geographic information systems, plotting 149 earthquake points from 1958 to 1920, planning evacuation routes for earthquake and tsunami disaster mitigation, as well as measuring coordinates, height, slope, and width between the coast and settlements, tourist attractions, main roads south of West Java, and evaluation of existing evacuation routes so that the community has an evacuation route adequate and safe.